Assessment of bacterial endosymbionts and the host, Bemisia tabaci (Hemiptera: Aleyrodidae), using rRNA and mitochondrial cytochrome oxidase I gene sequences. Issue 1 (2nd January 2018) - Hashmi, Tahseen Raza; Devi, Salam Rita; Meshram, Naresh M.; Prasad, Ram
ABSTRACT: Endosymbionts are vital factor for arthropod ecology. The whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) is a cryptic species complex composed of more than 34 putative species. Moreover to the primary endosymbiont Portiera aleyrodidarum, six secondary endosymbionts Cardinium, Arsenophonus, Rickettsia, Wolbachia, Hamiltonella and Fritschea are known in B . tabaci . Here, we tested four of the six secondary endosymbiont lineages (excluding Fritschea and Hamiltonella ) from 180 whitely individuals collected from six host plants belonging to families Solanaceae (Brinjal, Tomato and Potato) and Fabaceae (Soyabean, Mungbean and Subabool). Phylogenetic studies grounded on the mitochondrial cytochrome I gene revealed the presence of Asia 1, Asia II 1 and Asia II 7 genetic groups for B. tabaci . Specific primers targeting 16S rRNA and 23S rRNA gene were used for estimating the bacterial endosymbionts. As a primary endosymbiont Portiera aleyrodidarum was present in all the studied samples; whereas, an uneven distribution of secondary endosymbionts were recorded. Overall our finding exposes the variation and diversity of endosymbionts within the B. tabaci collected from different host plants and outlines the genetic groups of the insect pest. The study delivers a significant information concerning the circulation of secondary endosymbionts with host preferences of B. tabaci and provides suggestion for progressive studies on targeting the specific endosymbionts with respect to host for the control measures.